Ekstremisme Agama dalam Gerakan Islamic State of Iraq dan Syria (ISIS): Satu Analisis terhadap Akhbar The Star = (Religious Extremism in the Islamic State of Iraq and Syria (ISIS) Movement: An Analysis of The Star Newspaper) - Yusof, N.; Ghazali, M.H.I.; Hashim, R.A.; Mohd Sani, M.A.; Dalib, S.; Ramli, R.; Kaur, A.; Yusof, N. (Universiti Kebangsaan Malaysia Press, 2017)
The study aims to investigate the issues of extremism of the Islamic State of Iraq and Syria (ISIS) movement in the English-language newspaper, The Star, over a two-year period from January 2015 to December 2016. Religious extremism is an important issue in dealing with the unity and security of a nation. Globalization has raised religious extremism to a larger scale. In the context of this study, an extremist organization such as ISIS is seen as a threat to a country as there are various tragic cases in the world that are associated with this group. There are studies exploring religious extremism in Malaysia but not specifically in the field of communication. Thus, this study explores the issue of religious extremism in the print media in Malaysia. Specifically, there are two objectives of the study: i) identifying news themes of extremism and, ii) identifying the direction of the news. Using content analysis method, 40 news stories have been analyzed. The findings revealed 13 issues that were derived from 3 main themes. The majority of news reporting on ISIS was negative. This study contributes to social implications on the importance of understanding the theme and direction of news about religious extremism in Malaysia that has a global impact. This is an exploratory study on the issue of extremism in the English newspaper that has the highest circulation in Malaysia.